A Playground for ALL Children - Tavares, M. C. (Open Schools Journal for Open Science, 2020)
As all children deserve the same opportunity to play with each other and to be happy in their differences, students from the class 3.ºB, of Santo Amaro Elementary School, want the school playground to be inclusive, for children in a wheelchair. At the beginning of the project, children in a wheelchair could not play together with their colleagues, as the playground equipment was not adapted. Students developed research on inclusion, built models, and contacted architects that are specialized in inclusive playgrounds. Students also engaged their families in the development of the project. The next step is to show the project to the local authorities.